(untitled) (Global Journal of Management and Business Research, 2020)
The role of teachers is of utmost significance in the education system. The emotions of teachers play a vital role in determining their development and wellbeing. Emotional dissonance leads to several negative consequences for both the teachers and the institution and will affect their commitment and overall well-being. Several factors affect the emotions of teachers in the institution. This emotional exhaustion of the teachers can be reduced if the organization has inclusive leaders, provides them a climate of empowerment and follows justice.